Construction of pY-Af Vector for Expression of Thermostable α-L-Arabinofuranosidase in Saccharomyces cerevisiae - I Nengah Wirajana; Ni Nyoman Tri Puspaningsih; Eddy Bagus Wasito; Soekry Erfan Kusuma; Tetsuya Kimura; Kazuo Sakka (ANNALES BOGORIENSES, 2010)
In this research,  construction  of expression  vector  for thermostable α -L-arabinofuranosidase  in Saccharomyces cerevisiae was conducted. BJ1824 was conducted The  Escherichia coli/S. cerevisiae  shuttle vector, pYES2 was  used  as  parental  vector  in  construction.  The  abfA  gene  encoding  α-L- arabinofuranosidase  from Geobacillus  thermoleovorans  IT-08  was  amplified  by  PCR,  in  which  the  plasmid  pTP510 was  used  as  a template. The amplification product was treated with  SacI and XhoI and then subcloned to the pYES2 vector, which was previously digested with  SacI and  XhoI. The recombinant plasmid was designated as pY-Af and propagated  first  in  E.  coli  Top 10,  and  then  transformed  into  S.  cerevisiae  BJ1824.  For  α- Larabinofuranosidase (AbfA) production, the yeast transformants were grown in YNBG selective medium and YPG rich medium, using galactose as an inducer. The AbfA activity was assayed by measuring the amount of p-nitrophenol (pNP) released  from  p-nitrophenyl-α-L-arabinofuranoside  (pNPA) substrate at pH 6.0 and 70 C  for  30  min.  The  recombinant  AbfA  activity  was  detected  in  either  of  culture  medium  (0.98%),  cellassociated (14.17%) and intracellular (84.85%) when recombinant yeast was grown in YPG rich medium.Key words: α-L-arabinofuranosidase; Saccharomyces cerevisiae; expression vector